1991
DOI: 10.1247/csf.16.419
|View full text |Cite
|
Sign up to set email alerts
|

Stacks of Flattened Smooth Endoplasmic Reticulum Highly Enriched in Inositol 1,4,5-Trisphosphate(InsP3)Receptor in Mouse Cerebellar Purkinje Cells.

Abstract: ABSTRACT. By immunogoldelectron microscopy we have shown that in mouse cerebellar Purkinje cells fixed by per fusion with formaldehyde-glutaraldehyde solution, the InsP3 receptor are numeously detected on the stacks of flattened cisterns (OTSUet al, (1990) CellStruct. Funct. , 15: 163-173). In the present experiment we investigated distribution, structure and properties of the stacks by conventional electronmicroscopy, lectin cytochemistry and immunoelectron microscopy. The size and number of stacks were varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Mammalian Purkinje cells show a high level of IP 3 binding activity (Worley et al, 1989) and express a high density of IP 3 R protein associated with the ER (Mignery et al, 1989;Otsu et al, 1990;Nakanishi et al, 1991;Yamamoto et al, 1991;Furuichi et al, 1993;Suburo et al, 1993;Sharp et al, 1993;Miyata et al, 1999). Typically, Purkinje cells of the cerebellum show the highest label intensity for IP 3 R throughout the central nervous system and express the IP 3 R protein intracellularly in all compartments (axon, soma, dendrites) with the exception Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammalian Purkinje cells show a high level of IP 3 binding activity (Worley et al, 1989) and express a high density of IP 3 R protein associated with the ER (Mignery et al, 1989;Otsu et al, 1990;Nakanishi et al, 1991;Yamamoto et al, 1991;Furuichi et al, 1993;Suburo et al, 1993;Sharp et al, 1993;Miyata et al, 1999). Typically, Purkinje cells of the cerebellum show the highest label intensity for IP 3 R throughout the central nervous system and express the IP 3 R protein intracellularly in all compartments (axon, soma, dendrites) with the exception Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that used mammalian cerebella clearly showed the presence of all major components of IP 3 -mediated Ca release using a variety of different techniques (Nakanishi et al, 1991;Watras et al, 1991;Eilers et al, 1996;Finch and Augustine, 1998). Indeed, the IP 3 R is expressed at very high levels on the ER of mammalian cerebellar Purkinje neurons (Otsu et al, 1990;Yamamoto et al, 1991;Yamada et al, 1992). The present study had three aims: 1) to characterize further the distribution of IP 3 R type 1 (IP 3 R1) in mammalian cerebella by determining its localization in hamster and comparing it to that of two other rodent species, rat and mouse; 2) to localize the IP 3 R1 in cerebella of zebrafish Danio rerio, claw frog Xenopus laevis and skate Raja erinacea, vertebrate species that are important model animals in neurogenetics or neurophysiology; and 3) to compare the cerebellar localization pattern of IP 3 R1 immunoreactivity in different vertebrate phyla.…”
mentioning
confidence: 99%
“…Immunoelectron Microscopy-Cryo-ultramicrotomy and immunogold staining were followed as described previously (14) with a slight modification. Briefly, cells were fixed in 4% paraformaldehyde and 0.2% glutaraldehyde in 0.1 M sodium phosphate buffer, pH 7.4, for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…For immunoelectron microscopy, the post-embedding immunogold method was used to label cultured cells embedded in LR white resin (London Resin Co.) as previously described (Yamamoto et al, 1991).…”
Section: Electron Microscopymentioning
confidence: 99%